Digitalization of Islamic Politics in Indonesia: A Critical Study of Religion-Based Political Parties - Anang Setiawan; Aqil Teguh Fathani; Maisarah Mitra Adrian; Muhammad Rafli Ramadhan (Universitas Indo Global Mandiri, 2026)
Purpose : This study examines how Islamic political parties in Indonesia (PKS, PKB, and PPP) transform their strategies and ideological articulation in response to digitalization by analyzing political communication on X (Twitter), Instagram, YouTube, and TikTok, with particular attention to the implications of religious symbols in online politics. Design/Methodology : Using a critical qualitative approach grounded in Norman Fairclough’s Critical Discourse Analysis (CDA), the study analyzes primary data consisting of official party posts and user comments to identify textual patterns, discursive practices, identity negotiations, and the articulation of Islamic values across platform-specific formats. The findings show that these parties strategically integrate rich religious narratives and symbols tailored to each platform’s affordances to build political image, strengthen ideological positioning, and mobilize support. Religion-based content consistently generates higher public engagement, indicating strong ideological resonance between party messages and segments of the audience. However, this digitalization also prompts criticism regarding the commodification of religious identity and the normalization of a singular political-religious identity, which may narrow deliberative space, intensify polarization, and weaken pluralism in the digital public sphere. Practically, the study recommends a more ethical and reflective approach to digital da’wah and religious political communication—emphasizing inclusive framing, transparency of intent, and dialogic engagement—to maintain a democratic and pluralistic online environment. Originality lies in its comparative cross-platform CDA of three Islamic parties that connects platform-specific communication strategies with audience engagement and democratic implications in contemporary Indonesia.